A Development Model of School Administration Towards the Next Normal - Puthaprasert, Choocheep; Supising, Jiraporn; Thammachai, Prapan; Kosanpipat, Sirimas; Phuvipadawat, Somsak; Muntabutara, Suwan (Community and Social Development Journal, 2023)
The objectives of this research were: 1) to investigate the current state and problems of school administration in the new normal to prepare the school for the next normal; 2) to analyze success factors and conditions of school administration towards the next normal; 3) to develop a model for school administration towards the next normal, and 4) to propose policy proposals and practical guidelines for school administration towards the next normal. The research was divided into four phases, as follows: 1) investigate the current state and problems in the new normal by using an in-depth interview with 29 administrators; 2) analyze the success factors and conditions by participating in the workshop of 11 informants; 3) develop a model by constructing, verifying, and evaluating it by attending connoisseurship; and 4) propose policy proposals and practical guidelines by conducting brainstorming discussions with 15 experts and a research team. The research results were as follows: 1) the current state and problems in the new normal have seven components: 1) Planning (P), 2) Organizing (O), 3) Staffing (S), 4) Directing (D), 5) Coordinating (C), 6) Reporting (R), and 7) Budgeting (B); 2) the success factors and conditions were administrators, educators, and school boards must work together to ensure the overall academic progress of students, technology, and communications were playing an important role in helping people adapt to the next normal; 3) a model consisted of a principle, objectives, operational approaches, an evaluation, and conditions for achievement; and 4) policy proposal and practical guidelines were the government should implement an entirely new policy to establish strategies for school administration towards the next normal and the Office of the Basic Education Commission (OBEC) and directors of the Educational Service Area should lead the school administrators and affiliate agencies to apply strategies into practices for school administration towards the next normal.